Cryopreservation: An Overview of Principles and Cell-Specific Considerations - Whaley, David; Damyar, Kimia; Witek, Rafal P.; Mendoza, Alan; Alexander, Michael; Lakey, Jonathan RT (Cell transplantation, 2021)
The origins of low-temperature tissue storage research date back to the late 1800s. Over half a century later, osmotic stress was revealed to be a main contributor to cell death during cryopreservation. Consequently, the addition of cryoprotective agents (CPAs) such as dimethyl sulfoxide (DMSO), glycerol (GLY), ethylene glycol (EG), or propylene glycol (PG), although toxic to cells at high concentrations, was identified as a necessary step to protect against rampant cell death during cryopreservation. In addition to osmotic stress, cooling and thawing rates were also shown to have significant influence on cell survival during low temperature storage. In general, successful low-temperature cell preservation consists of the addition of a CPA (commonly 10% DMSO), alone or in combination with additional permeating or non-permeating agents, cooling rates of approximately 1ºC/min, and storage in either liquid or vapor phase nitrogen. In addition to general considerations, cell-specific recommendations for hepatocytes, pancreatic islets, sperm, oocytes, and stem cells should be observed to maximize yields. For example, rapid cooling is associated with better cryopreservation outcomes for oocytes, pancreatic islets, and embryonic stem cells while slow cooling is recommended for cryopreservation of hepatocytes, hematopoietic stem cells, and mesenchymal stem cells. Yields can be further maximized by implementing additional pre-cryo steps such as: pre-incubation with glucose and anti-oxidants, alginate encapsulation, and selecting cells within an optimal age range and functional ability. Finally, viability and functional assays are critical steps in determining the quality of the cells post-thaw and improving the efficiency of the current cryopreservation methods.